2009
DOI: 10.1051/apido/2008072
|View full text |Cite
|
Sign up to set email alerts
|

Confirmation of phenolic acids and flavonoids in honeys by UPLC-MS

Abstract: -Certain phenolic acids and flavonoids are described in the literature as marker substances for several unifloral honeys. As not all authors utilised the same methods for extraction and determination, there are remarkable discrepancies in the published data concerning these substances. Ethyl acetate extracts which, aside from phenolic acids, also contain flavonoids were analysed by Ultra Performance Liquid Chromatography-Quadrupole/Time of flight-mass spectrometry (UPLC-Q/TOF-MS). First, the mass spectra of 37… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(47 citation statements)
references
References 22 publications
4
33
0
1
Order By: Relevance
“…On the other side, gallic acid was detected in all honeydew honey samples and the highest value was observed in S5 sample to be 2.95 mg=kg. Trautvetter and others [21] investigated that the phenolic acids and flavonoids of honeydew, sun-flower, lime, rape, and clover honeys by UPLC-MS and similarly to our results they found that the amount of gallic acid in honeydew honeys were to be 100-2000 counts and the amount of quercetin was lower than 100 counts. However, in our study the percentage of gallic acid in honeydew honeys was lower than the percentages of catechin, epicatechin, and coumaric acid ( Figure 1A).…”
Section: Resultssupporting
confidence: 85%
“…On the other side, gallic acid was detected in all honeydew honey samples and the highest value was observed in S5 sample to be 2.95 mg=kg. Trautvetter and others [21] investigated that the phenolic acids and flavonoids of honeydew, sun-flower, lime, rape, and clover honeys by UPLC-MS and similarly to our results they found that the amount of gallic acid in honeydew honeys were to be 100-2000 counts and the amount of quercetin was lower than 100 counts. However, in our study the percentage of gallic acid in honeydew honeys was lower than the percentages of catechin, epicatechin, and coumaric acid ( Figure 1A).…”
Section: Resultssupporting
confidence: 85%
“…Tested raw rape honey contained several phenolic compounds in its composition: Mainly hydroxybenzoic acid derivatives and some flavonoid aglycones (quercetin, kaempferol, and pinobanksin). Similarly, Trautvetter et al [33] found hydroxybenzoic acid derivatives as dominant compounds in rape honey, and also identified apigenin and chrysin among flavonoids.…”
Section: Experiments 2: Addition Of Mulberry Leaves and Fruits During mentioning
confidence: 90%
“…The main goal of sample preparation is to obtain an extract containing all the components of interest, as well as to separate the substances that could obstruct the determination of polyphenols (51). The methods commonly used for isolating polyphenols from honey ( Table 2; 15,28,31,42,46, are based on several types of extraction: liquid-liquid extraction (LLE), SPE, and adsorption on Amberlite XAD adsorbent polymer in combination with LLE or SPE (11).…”
Section: Extraction and Identification Of Polyphenols From Honey Samplesmentioning
confidence: 99%